PENGEMBANGAN MEDIA PEMBELAJARAN BERBASIS AUGMENTED REALITY UNTUK MEMBANTU MEMBACA PEMAHAMAN KELAS IV SD NEGERI 1 LANGSA - Juliati; Intan Purnama Dewi; Ronald Fransyaigu (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
In learning the role of media is very important. Reading comprehension of grade IV students of SD Negeri 1 Langsa shows that there is still a low level of reading comprehension. Augmented Reality-based learning media is one of the media that is suitable and appropriate to use to help read comprehension of students. The purpose of this study is to produce an Augmented Reality-based learning media product to help read comprehension grade IV SD Negeri 1 Langsa. This research is a development research (R&D) that refers to the modified level 3 Borg and Gall model with stages in the form of potential and problems, data collection, product design, design validation, design revision, and initial trials. The design of Augmented Reality-based learning media development consists of potential and problem stages, information collection and product design. The results of media validation obtained a feasibility test value of 98.43% and material expert validation of 93.75% with very feasible criteria. The results of practicality obtained a practicality value of 89.70% occupying very practical criteria with the meaning that it is easy to use.